Peranan Sektor Perikanan dan Kelautan Dalam Perekonomian Wilayah Propinsi Riau - Tince Sofyani (Ilmu Perairan (Aquatic Science), 2010)
The objective of this study is to investigate the role of fishery sector ineconomic regional of Riau Province. Data showed that the contribution of fisherysector to PDRB of Riau province is relatively small, namely 3,80 % in 2003 and thandecreasing until 3,70 % in 2007. At the same period fishery sector contribution 3,24% and than decreasing until 1,78 % for available employment in Riau Province.Fishery sector included economic base of Riau Province, during period 2003-2004fishery sector is base sector for available employment, but period 2005-2007 nonbase sector. Fishery sector have the income multiplier effect is relatively high, but thedecreasing from 32,32 in 2003 until 28,66 in 2007. Multiplier effect for availableemployment is 80,10 in 2003 – 2004. Regarding the potention of fishery is relativelybig, whereas the level of its exploitation have not been optimal, so fishery sector isimportant to be a priority in regional economic development in Riau Province.